Associations Between Circulating Insulin-Like Growth Factor 1 and Mortality in Women With Invasive Breast Cancer - Zhu, Yifei; Wang, Tiange; Wu, Jiayi; Huang, Ou; Zhu, Li; He, Jianrong; Li, Yafen; Chen, Weiguo; Chen, Xiaosong; Shen, Kunwei (Frontiers in Oncology, 2020)
Background: Studies on the association between circulating insulin-like growth factor 1 (IGF1) and prognosis of breast cancer are limited. Whether this association is modified by insulin levels and clinical characteristics is unclear. Methods: Serum concentrations of IGF1 as well as IGF binding protein 3 (IGFBP3), IGF1/IGFBP3 ratio, insulin, and C-peptide were prospectively examined in 2682 invasive breast cancer patients who received surgery in Ruijin Hospital, Shanghai, between 2012 and 2017. Cox proportional hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause mortality, breast cancer-specific mortality, and breast cancer recurrence associated with different levels of IGF1 and other biomarkers with multivariable adjustment. Results: Compared with patients with low IGF1, patients with high IGF1 had a significantly lower risk of all-cause mortality (HR, 0.53; 95% CI, 0.29-0.96) and a borderline lower risk of breast cancer-specific mortality (0.53; 0.27-1.02). The inverse association between IGF1 and all-cause mortality was consistent across stratification subgroups, but was more pronounced among patients with high insulin (HR, 0.40; 95% CI, 0.18-0.89), were premenopausal (0.34; 0.12-0.97), with tumor size > 2 cm (0.35; 0.17-0.73), with positive lymph node (0.49; 0.25-0.98), and with high Ki-67 level (0.49; 0.26-0.95) (all P for interaction > 0.05). No significant associations were found for IGFBP3, IGF1/IGFBP3 ratio, insulin, and C-peptide levels with all-cause mortality, breast cancer-specific mortality, and breast cancer recurrence. Conclusion: Circulating IGF1 was inversely and independently associated with all-cause mortality in invasive breast cancer patients, and this association was consistent across clinical risk factors.